THE INDONESIA-TIMOR LESTE BORDER ISSUES IN NUSA TENGGARA TIMUR PROVINCE - Kennedy, Posma S.J.K.; L.Tobing, Suzanna Josephine; Lumbantoruan, Rutman; Tampubolon, Emma (Universitas Kristen Indonesia, 2019)
This paper aims to look at various strategic issues which are problems that exist in the Indonesia-Timor Leste border region in East Nusa Tenggara Province, both in the determination and affirmation of border areas, as well as economic, natural resource and environmental issues, conditions infrastructure, and population, social and cultural conditions. This paper uses qualitative methods, through documentation and literature tracing, with the primary source of National Border Management Regulation No. 1/2011 on the Design of State Border Management No. 1/2015 on the 2015-2019 State Border Management Master Plan. Strategic issues in managing border areas are mainly in the aspects of setting and affirming national boundaries and perspectives of enhancing defense and security and law enforcement. While the strategic issues concerning the land border area of Indonesia-Timor Leste in the Province of East Nusa Tenggara mainly regard economic conditions, natural resources and the environment, infrastructure conditions, and population, social and cultural conditions. Keywords: Border Area, Land Border, East Nusa Tenggara, Timor Leste